Rezension von: Heinzer, Felix, Gold in the Sanctuary - Schaab, Rupert (Zeitschrift für Württembergische Landesgeschichte, 2023)
Felix Heinzer, Gold in the Sanctuary. Reassessing Notker of St Gall’s Liber Ymnorum (Studies and texts 228). Toronto: PIMS 2022. 322 S. ISBN 978-0888442284. Ln. € 99,–